An Extensive Pharmacological Evaluation of New Anti-carcinoma CDK1 and SERPINE1 Targeted Compound Homoorientin from T. officinale's with In-depth Molecular Docking and Simulation Studies - Shaikh, Abdul Lateef; Zhou, Lin; Zheng, Shusen (Current Medicinal Chemistry, 2026)
IntroductionHepatitis B Virus-Related Hepatocellular Carcinoma (HBV-HCC) constitutes a formidable global health challenge, demanding an in-depth understanding of its intricate pathogenesis. The research conducted a comprehensive analysis of the multifaceted relationship between HBV-HCC. It further examined the potential of Taraxacum officinale, which could serve as an effective adjunct therapy in treating HBV-associated HCC. Our approach integrates network pharmacology, pathway analysis, molecular docking, and dynamics simulations, offering an intricate unraveling of the molecular mechanisms that underlie T. officinale's potential impact on HBV-HCC.MethodsAdditionally, we delve into microarray analysis to unearth differentially expressed genes (DEGs) associated with HBV-HCC, molecular docking to validate compound interactions with key proteins, and molecular dynamics simulations to elucidate the stability of these interactions. These multifaceted approaches enhance our understanding of T. officinale's therapeutic potential.ResultsThis work represents a significant advancement toward the development of more effective strategies for the management of this challenging disease, offering a comprehensive exploration of T. officinale's therapeutic prowess. Within this multidimensional framework, we identify CDK1, SERPINE1, and PTGS2 as promising therapeutic targets, shedding light on the molecular intricacies of disease progression. Further, Homoorientin from T. officinale's demonstrates a strong binding affinity with proteins CDK1, SERPINE1, and PTGS2, suggesting a potential synergistic effect in therapeutic applications. Moreover, our enrichment analysis uncovers a rich tapestry of pathways enriched in HBV-HCC, providing insights into the multifaceted landscape of disease complexity.ConclusionThese findings not only pave the way for potential targeted therapies but also deepen our comprehension of the intricate molecular underpinnings of HBV-HCC.This work represents a significant advancement toward the development of more effective strategies for the management of this challenging disease, offering a multifaceted exploration of T. officinale's therapeutic potential.
Keywords: T. officinale